Long‐term follow‐up of children with haemophilia – low incidence of infections with central venous access devices. (27th January 2015) - Harroche, A.; Merckx, J.; Salvi, N.; Faivre, J.; Jacqmarcq, O.; Dazet, D.; Makhloufi, M.; Clairicia, M.; Torchet, M.‐F.; Aouba, A.; Rothschild, C.
Summary This study reports on 15 years of experience, in a single haemophilia care centre in France, with central venous access devices (VADs) in children with haemophilia. Following the insertion of a central VAD, patients were requested to return to the hospital on a quarterly basis for a multidisciplinary appointment which included clinical examination, chest X‐ray, cardiac and major vessels ultrasound and preventive fibrinolysis. The family was urged to return to the Haemophilia Care Centre if complications or problems occurred. The follow‐up comprised 50 patients. Data were collected prospectively. The total number of days with a VAD was 86 461 days and the total number of times the VAD was used was 41 192 (approximately every other day). Mean duration of VAD placement was 1269 days (range 113–2794 days). There were 25 complications, of which 9 haematomas and 5 systemic infections. Two VADs, infected with Staphylococcus aureus, had to be replaced. The infection rate was calculated as 0.0578 infections/1000 catheter days. There were no cases of thrombosis. This study concluded that most VAD infections in children can be avoided, even in patients requiring intense, prolonged treatment. The very low infection rate was achieved through the efforts of a multidisciplinary team, combined with extensive training for all individuals involved, adherence to written protocols and specific monitoring measures.